Resilience in Agricultural Product Industry and Supply Chain - Fang, Lina; Zhang, Xin (International Journal of Global Economics and Management, 2024)
Understanding the critical role resilience plays within agricultural supply chains, this paper embarks on an exhaustive exploration to delineate its significance. We delve into the theoretical underpinnings and conduct a comprehensive review of existing literature, highlighting the intricate dynamics that define resilience in the context of agricultural supply chains. Through meticulous methodology and insightful case studies, our research identifies key factors that enhance the robustness of these chains against disruptions. Our findings underscore the necessity of adaptive strategies, robust infrastructure, and collaborative networks for bolstering resilience. Conclusively, we articulate the implications of our study, outlining future directions for research and practice aimed at fortifying agricultural supply chains against vulnerabilities. This work contributes significantly to the discourse on enhancing agricultural supply chain resilience, offering actionable insights for policymakers, practitioners, and researchers alike.